Proteome and morphological analysis show unexpected differences between promastigotes of Leishmania amazonensis PH8 and LV79 strains. - Fabia Tomie Tano; Gustavo Rolim Barbosa; Eloiza de Rezende; Rodolpho Ornitz Oliveira Souza; Sandra Marcia Muxel; Ariel Mariano Silber; Giuseppe Palmisano; Beatriz Simonsen Stolf (PLoS ONE)
Background Leishmaniases are diseases caused by Leishmania protozoans that affect around 12 million people. Leishmania promastigotes are transmitted to vertebrates by female phlebotomine flies during their blood meal. Parasites attach to phagocytic cells, are phagocytosed and differentiate into amastigotes. We previously showed that PH8 and LV79 strains of Leishmania amazonensis have different virulence in mice and that their amastigotes differ in their proteomes. In this work, we compare promastigotes' infectivity in macrophages, their proteomes and morphologies. Methods/principal findings Phagocytosis assays showed that promastigotes adhesion to and phagocytosis by macrophages is higher in PH8 than LV79. To identify proteins that differ between the two strains and that may eventually contribute for these differences we used a label-free proteomic approach to compare promastigote´s membrane-enriched fractions. Proteomic analysis enabled precise discrimination of PH8 and LV79 protein profiles and the identification of several differentially abundant proteins. The proteins more abundant in LV79 promastigotes participate mainly in translation and amino acid and nucleotide metabolism, while the more abundant in PH8 are involved in carbohydrate metabolism, cytoskeleton composition and vesicle/membrane trafficking. Interestingly, although the virulence factor GP63 was more abundant in the less virulent LV79 strain, zymography suggests a higher protease activity in PH8. Enolase, which may be related to virulence, was more abundant in PH8 promastigotes. Unexpectedly, flow cytometry and morphometric analysis indicate higher abundance of metacyclics in LV79. Conclusions/significance Proteome comparison of PH8 and LV79 promastigotes generated a list of differential proteins, some of which may be further prospected to affect the infectivity of promastigotes. Although proteomic profile of PH8 includes more proteins characteristic of metacyclics, flow cytometry and morphometric analysis indicate a higher abundance of metacyclics in LV79 cultures. These results shed light to the gaps in our knowledge of metacyclogenesis in L. amazonensis, and to proteins that should be studied in the context of infection by this species.